Thermal Design of Pre-installed Power Room for Photovoltaic Megawatt-level-inverter - MEI Xingliang; LIAO Yuanhui; WU Jianxiong; LIU Yuzhu (Kongzhi Yu Xinxi Jishu)
It analyzed the problem of ventilation and heat dissipation of photovoltaic (PV) megawatt-level-inverter power room and presented an optimized design of air duct, in wihich an independent air duct was constructed for power unit that generated a large quantity of heat, air velocity of auxiliary air duct was dectreased and air inlet structure was simplified. Therefore, the air inlet can resist harsh conditions and has lower cost. The theoretic calculation was carried out for the fan’s parameters. Simulation and test results show that the optimized design of power room for (PV) megawatt-level-inverter can meet the thermal requirements of the system completely.